(untitled) (Research, Society and Development, 2022)
Uncaria tomentosa (Cat’s Claw) is widely used by the Brazilian population because it is easy to acquire, so understanding its toxicological effects helps to avoid harmful action caused by its constituents. The toxicity of these substances can be analyzed by several methods that use in vitro, in vivo, ex vivo and in silico models. In this context, we sought to evaluate the toxicity of Uncaria tomentosa. The present study was an integrative literature review, in which articles were selected from the PubMed/Medline, LILACS, Science Direct and SciELO databases, during the period from August 2002 to August 2022. The results point out that Uncaria tomentosa is not genotoxic, but is cytotoxic, both in the analyzes carried out with its aqueous and hydroethanolic extracts (water and ethanol), and its substances obtained from the isolation of extracts such as alkaloids and glycosides, evaluated in several study models such as non-neoplastic and neoplastic human cells, Drosophila melanogaster, cells from Wistar rats, cells from mice and zebrafish (Danio rerio). In addition to its possible antimutagenic and antigenotoxic action, it has a protective activity against DNA damage possibly related to its substances such as alkaloids and glycosides present in the extracts that can play an antioxidant role in isolation or with a synergistic effect, fighting free radicals. Therefore, Uncaria tomentosa presents a safe use regarding its toxicity.